Consumul populației din România în ultimele două decenii - Stanciu, Mariana (Calitatea Vieții, 2010)
During the last century, the developed European nations have shifted from societies where people defined themselves by what they produce, to societies where consumption gives the major means of self identity. Romanian people started to do it from only two decades ago... This article is about the trends in the field of consumption goods and services in Romania of last twenty years.